Analysis of User Experience in E-learning Implementation in Higher Education: A Case Study on Students UKI Toraja - Sampelolo, Rigel; Lestari, Dian Hardianti Eka; Pahmi, Zul; Pratama, Muh. Putra Pratama Putra (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the application of e-learning in computer graphics courses. This research uses descriptive analysis methods with observation, interview and questionnaire techniques for students of the education technology study program at Universitas Kristen Indonesia Toraja class of 2021 who are randomly selected and descriptive techniques are used as analysis techniques. The results of the analysis show that students know e-learning, as many as 62% of students define e-learning as a learning that is done online (online) and the remaining 38% define e-learning as technology-based electronic learning. This study also concluded that 93.3% of students gave positive perceptions related to the activity of accessing materials.